2013
DOI: 10.1007/s00246-012-0618-8
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Rehabilitation Enhances Daily Physical Activity and Motor Skill in Children Who Have Undergone the Fontan Procedure

Abstract: This randomized trial compared physical activity enhancing exercise prescription and education programs in 61 children (36 male) with single-ventricle physiology after Fontan. After Fontan, children are less active than recommended for optimal health. They are often geographically dispersed and unable to attend weekday programs. Participants, 5.9-11.7 years of age who were status 5.3 years post-Fontan, received 12-month, parent-delivered home programs to enhance physical activity, motor skill, fitness, and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 32 publications
5
91
0
Order By: Relevance
“…These high levels of activity are likely explained by a combination of the very young age range (because PA decreases with age) and the researchers' use of a much lower accelerometry sampling interval (3 seconds), to capture the sporadic high‐intensity activity typical of young children, and a lower MVPA threshold; combined, these measures will lead to higher estimates of MVPA compared with our analytical approach. A study of Fontan patients (in Ontario, Canada; n≈60) reported mean estimates of MVPA that were similar to our sample (≈50 versus 49 min/day); these data are also based on 15‐second epoch, but the investigators used a different device and MVPA threshold, and it is of note that their sample was much younger than ours (6–12 years) . Another small study (in Milwaukee, Wisconsin) assessed MVPA across a range of CHD severities and found high levels of MVPA overall (≈70 min/day), despite using a lower sampling interval (30‐second epoch) and higher, metabolic equivalent–based MVPA (≥4 metabolic equivalents) thresholds that would yield lower estimates of MVPA compared with our approach.…”
Section: Discussionsupporting
confidence: 74%
“…These high levels of activity are likely explained by a combination of the very young age range (because PA decreases with age) and the researchers' use of a much lower accelerometry sampling interval (3 seconds), to capture the sporadic high‐intensity activity typical of young children, and a lower MVPA threshold; combined, these measures will lead to higher estimates of MVPA compared with our analytical approach. A study of Fontan patients (in Ontario, Canada; n≈60) reported mean estimates of MVPA that were similar to our sample (≈50 versus 49 min/day); these data are also based on 15‐second epoch, but the investigators used a different device and MVPA threshold, and it is of note that their sample was much younger than ours (6–12 years) . Another small study (in Milwaukee, Wisconsin) assessed MVPA across a range of CHD severities and found high levels of MVPA overall (≈70 min/day), despite using a lower sampling interval (30‐second epoch) and higher, metabolic equivalent–based MVPA (≥4 metabolic equivalents) thresholds that would yield lower estimates of MVPA compared with our approach.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, there was no change in activity attitudes, as assessed through verbal administration of Children's Self-Perception of Adequacy & Predilection for Physical Activity Scale. 28 Collectively, the results from our study and the previously discussed studies suggest that physical function HRQOL and exercise capacity is modifiable in patients with Fontan circulation and may improve with programs that encourage an increase in physical activity and exercise. Our study is unique in that the majority of participation was home-based, and thus the program could be completed by patients that reside long distances from our hospital center.…”
Section: Discussionsupporting
confidence: 61%
“…Exercise training may, also, have a positive effect on peripheral muscles in children with congenital heart disease (49). Rehabilitation programmes can also enhance physical activity levels in children with Fontan circulation (50). Performing exercise tests, taking part of exercise interventions, and seeing that physical activity is safe, is of importance for patients and their parents (51).…”
Section: Long-term Outcomementioning
confidence: 99%